No relation between afferent facilitation induced by digital nerve stimulation and the latency of cutaneomuscular reflexes and somatosensory evoked magnetic fields - Kojima, Sho; Onishi, Hideaki; Sugawara, Kazuhiro; Miyaguchi, Shota; Kirimoto, Hikari; Tamaki, Hiroyuki; Shirozu, Hiroshi; Kameyama, Shigeki (Frontiers in Human Neuroscience, 2014)
Primary motor cortex (M1) excitability can be assessed using transcranial magnetic stimulation (TMS) and can be modulated by a conditioning electrical stimulus delivered to a peripheral nerve prior to TMS. This is known as afferent facilitation (AF). The aim of this study was to determine whether AF can be induced by digital nerve stimulation and to evaluate the relation between the interstimulus interval (ISI) required for AF and the latency of the E2 component of the cutaneomuscular reflex (CMR) and the prominent somatosensory evoked field (SEF) deflection that occurs approximately 70 ms after digital nerve stimulation (P60m). Stimulation of the digital nerve of the right index finger was followed, at various time intervals, by single-pulse TMS applied to the contralateral hemisphere. The ISI between digital nerve stimulation and TMS was 20, 30, 40, 50, 60, 70, 80, 100, 140, 180, 200, or 220 ms. Single-pulse TMS was performed alone as a control. SEFs were recorded following digital nerve stimulation of the index finger, and the equivalent current dipole of prominent deflections that occurred around 70 ms after the stimulation was calculated. CMRs were recorded following digital nerve stimulation during muscle contraction. Motor evoked potentials were facilitated at an ISI between 50 and 100 ms in 11 of 13 subjects, and the facilitated MEP amplitude was larger than the unconditioned MEP amplitude (p < 0.01). There was no significant correlation between the ISI at which AF was maximal and the latency of the P60m component of the SEF (r = -0.50, p = 0.12) or the E2 component of the CMR (r = -0.54, p = 0.88). These results indicate that the precise ISI required for AF cannot be predicted using SEF or CMR.